2023
DOI: 10.3390/molecules28062501
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polycaprolactone/Chitosan Nanofibers Containing Cordia myxa Fruit Extract as Potential Biocompatible Antibacterial Wound Dressings

Abstract: The goal of the current work was to create an antibacterial agent by using polycaprolactone/chitosan (PCL/CH) nanofibers loaded with Cordia myxa fruit extract (CMFE) as an antimicrobial agent for wound dressing. Several characteristics, including morphological, physicomechanical, and mechanical characteristics, surface wettability, antibacterial activity, cell viability, and in vitro drug release, were investigated. The inclusion of CMFE in PCL/CH led to increased swelling capability and maximum weight loss. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The C=N- (azomethine) stretching frequency of the ligand showed a strong absorbance peak at 1643 cm −1 ; a shift toward the higher wavelength region (1610–1635 cm −1 ) of the metal(II) complexes revealed that the azomethine nitrogen had coordinated with metal ions ( Table 2 ) [ 21 ]. The bands at (1570–1590 cm −1 ) and (1350–1380 cm −1 ) were attributed to the asymmetric and symmetric vibrational frequencies, respectively, of the carboxyl groups present in the amino acid [ 22 , 23 , 24 , 25 ]. The absence of a band in the 1700–1750 cm −1 region suggested that the COO − group of L-valine was coordinated with the central metal ion and that the difference in the frequency value between the asymmetric and symmetric stretching vibrations of the complexes lay between 180 and 216 cm −1 , for which the latter is practically larger than that of a free carboxylate ion [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The C=N- (azomethine) stretching frequency of the ligand showed a strong absorbance peak at 1643 cm −1 ; a shift toward the higher wavelength region (1610–1635 cm −1 ) of the metal(II) complexes revealed that the azomethine nitrogen had coordinated with metal ions ( Table 2 ) [ 21 ]. The bands at (1570–1590 cm −1 ) and (1350–1380 cm −1 ) were attributed to the asymmetric and symmetric vibrational frequencies, respectively, of the carboxyl groups present in the amino acid [ 22 , 23 , 24 , 25 ]. The absence of a band in the 1700–1750 cm −1 region suggested that the COO − group of L-valine was coordinated with the central metal ion and that the difference in the frequency value between the asymmetric and symmetric stretching vibrations of the complexes lay between 180 and 216 cm −1 , for which the latter is practically larger than that of a free carboxylate ion [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectrometric method was used to obtain the IR spectrum of the synthesized complexes in the 400–4000 cm –1 range in ethanol. The peak annotations of the present complexes are summarized in Table . The O-H stretching band was not detected at 3350 cm –1 , which proposes that phenolic O–H is deprotonated because of complex generation.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro antibacterial assay of metal­(II) complexes was tested against Enterococcus faecalis, Staphylococcus aureus, Klebsiella pneumonia, and Acinetobacter baumannii pathogens. , The zone of inhibition was measured for prepared complexes by the disc diffusion method, and their observation revealed that the complexes had significant antibacterial activity, as described in Figure , and their inhibition diameters are depicted in Table .…”
Section: Resultsmentioning
confidence: 99%
“…[12] The need for efficient tissue engineering products is constantly increasing, mainly due to the threat of the development of bacterial resistance to a wide range of antibacterial drugs commonly used in wound treatment. [13] The pH of human skin is generally a negligible physiological parameter, although it has a significant influence on the wound healing process. Healthy skin is slightly acidic with a pH in the range of 4-6, [14] but when injury occurs, the pH shifts to alkaline (up to 8.5).…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] The need for efficient tissue engineering products is constantly increasing, mainly due to the threat of the development of bacterial resistance to a wide range of antibacterial drugs commonly used in wound treatment. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%